1972
DOI: 10.1002/pen.760120206
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet depolymerization of photoresist polymers

Abstract: A new method for removal of thin films of photoresist polymers has been found. When polymeric films are exposed to ultraviolet light in the presence of air, the material can be removed leaving an extremely clean surface, free of carbonaceous material. This process has been examined for a variety of photoresist polymers as well as on nonphotoresist polymers and on a variety of substrates. The process offers a new method of photoresist removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1972
1972
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…We used a total of five silicon nitride probes (DNP, Veeco Instruments Inc., Santa Barbara, CA) with measured spring constants of 0.12 N/m Ϯ 10%, resonance frequencies of ϳ5 kHz in liquid, and average radii of 40 nm (previously measured by electron microscopy; data not shown). Probes were immersed in 100% ethanol for 12 h and then subjected to UV treatment (365 nm) to remove organic films (4,38). AFM experiments were performed with ultrapure water.…”
Section: Methodsmentioning
confidence: 99%
“…We used a total of five silicon nitride probes (DNP, Veeco Instruments Inc., Santa Barbara, CA) with measured spring constants of 0.12 N/m Ϯ 10%, resonance frequencies of ϳ5 kHz in liquid, and average radii of 40 nm (previously measured by electron microscopy; data not shown). Probes were immersed in 100% ethanol for 12 h and then subjected to UV treatment (365 nm) to remove organic films (4,38). AFM experiments were performed with ultrapure water.…”
Section: Methodsmentioning
confidence: 99%
“…This method is derived from a UV/ ozone exposure technique originally developed for the removal of organic contaminants from semiconductors as an alternative to oxygen plasma ashing (Bolon and Kunz 1972;Sowell et al 1974;Vig and LeBus 1976;Vig 1985). Using a low-pressure mercury lamp to expose a substrate in an air-filled chamber at atmospheric pressure, light output at a wavelength of 184.9 nm is absorbed by oxygen in the air, resulting in the generation of ozone.…”
Section: Surface Treatment and Modificationmentioning
confidence: 99%
“…Bolon and Kunz [13] reported that exposure to ultraviolet light (UV) in an oxygen atmosphere leads to the depolymerization of photoresist polymers. The UV treatment has been widely used as an effective method of decomposing hydrocarbons on substrates [14,15].…”
Section: Introductionmentioning
confidence: 99%